FORMAL AND INFORMAL MEDIA EDUCATION IN UKRAINE: PROBLEMS AND PROSPECTS - Kondur, Oksana; Didukh, Iryna (Mountain School of Ukrainian Carpaty, 2023)
The article examines the current state of development of formal and non-formal media education in the Ukrainian educational space. A comprehensive analysis of the formal and informal aspects of the media education paradigm is carried out, and the key areas of their development are identified. The formal and non-formal aspects of media education are systematized, taking into account its impact on the development of media literacy and critical thinking of participants in the educational process. The media education experience and best practices of media education activities in formal and nonformal education in Ukraine are highlighted. It is determined that the media is one of the factors in the practical implementation of the theory of dialogue of cultures, and therefore acts as an important social institution of the modern information society. The current state of media literacy of teachers in Ukraine in the framework of formal and non-formal education is analyzed, and it is noted that the problem of media education requires scientific substantiation and the search for ways to modernize the system of professional development of scientific and pedagogical workers. The predominance of non-formal media education is obvious, but the availability and differentiation of media education programs provides teachers with a significant amount of opportunities for the development of personal and professional media culture. A modern teacher should become a generator of media literacy skills for participants in the educational process. Therefore, the value of teachers' media competence is gaining new importance for ensuring continuous education and sustainable development of Ukrainian society.